Why do students exhibit different attention-related behavior during instruction? Investigating effects of individual and context-dependent determinants. (February 2023) - Goldberg, Patricia; Wagner, Wolfgang; Seidel, Tina; Stürmer, Kathleen
Abstract: To determine the success of their instruction, teachers need to rely on observable cues in students' behavior. However, students exhibit different attention-related behavior within one lesson as well as compared with their peers. It is not yet clear to what extent these differences result from the design of classroom instruction and how individual and contextual factors determine students' behavior during instruction. In the present study, we applied a continuous behavior-rating system to 10 classroom videos and based our analysis on 1200 1-s intervals of N  = 199 students. Using dynamic structural equation modeling, students' attention-related behavior was primarily determined by contextual factors, stressing the important role of teachers but also the impact of factors that are unique in individual classrooms. Highlights: Momentary changes in students' learning behavior were investigated. Student behavior was studied using dynamic structural equation modeling. Students' behavior depended more on contextual than on their individual characteristics. Dynamics within classrooms are unique to the set of students and their teacher.